Cueva Antón: A multi-proxy MIS 3 to MIS 5a paleoenvironmental record for SE Iberia. (15th August 2016) - Zilhão, João; Ajas, Aurélie; Badal, Ernestina; Burow, Christoph; Kehl, Martin; López-Sáez, José Antonio; Pimenta, Carlos; Preece, Richard C.; Sanchis, Alfred; Sanz, Montserrat; Weniger, Gerd-Christian; White, Dustin; et al.
Abstract: Overlying a palustrine deposit of unknown age (complex FP), and protected from weathering and erosion inside a large cave/rock-shelter cavity, the sedimentary fill of Cueva Antón, a Middle Paleolithic site in SE Spain, corresponds in most part (sub-complexes AS2-to-AS5) to a ca.3 m-thick Upper Pleistocene terrace of the River Mula. Coupled with the constraints derived from the deposit's paleoclimatic proxies, OSL dating places the accumulation of this terrace in MIS 5a, and radiocarbon dates from the overlying breccia cum alluvium (sub-complex AS1) fall in the middle part of MIS 3; the intervening hiatus relates to valley incision and attendant erosion. The two intervals represented remain largely unknown in Iberia, where the archeology of the early-to-middle Upper Pleistocene is almost entirely derived from karst sites; Cueva Antón shows that this dearth of data, often interpreted in demographic terms, has depositional underpinnings ultimately determined by past climate variation. In early MIS 5a, the paleobotanical evidence indicates climate conditions similar to present, albeit wetter, followed by progressive cooling, reflected in the replacement of Aleppo pine by black pine and, at the very end, juniper-dominated landscapes — the latter characterizing also mid-MIS 3 times. The variation in sedimentary facies and composition of the mollusk assemblages reflects the changing position of the river channel relative to the back wall of the cave. Such changes represented the major constraint for the occupation of the site — most of the time inaccessible to terrestrial mammals, it was used throughout by the eagle-owl, explaining the abundance of rabbit bones. Human occupation occurred during a few, short windows of availability, and is reflected in well-preserved living floors defined by hearths, artefact scatters, and the remains of hunted herbivores. The stone tool assemblages are Middle Paleolithic, which, in Europe, implies a Neandertal identity for their makers and, hence, that Neandertals persisted in the region until GI 8. Cueva Antón's high-resolution record provides unique, critical information on the paleoenvironments and adaptations of humans in two short windows of time during which wetter conditions existed in SE Iberia, where arid or semi-arid climates prevailed through most of the Upper Pleistocene and the Holocene. Highlights: High-resolution continental record of environmental change. Wetter conditions during MIS 5a in a nowadays semi-arid region of Europe. Seasonal Middle Paleolithic camping in non-palimpsest contexts. Persistence of Neandertals up to GI 8 in SE Spain.